الموقف العُماني من المعاهدات البريطانية في تجارة الرقيق في شرق أفريقيا ودور فرنسا الثانوي فيها (1822-1873) - لفته, مثنى أيوب (الملوية للدراسات الآثارية والتاريخية, 2025)
The slave trade was a complex economic and political system closely connected to Omani influence along the East African coast, where Zanzibar became a major center for exporting enslaved people and employing them in the clove plantations that formed the backbone of the economy at the time. The Omani presence contributed to organizing this trade and developing its structure, making it an important source of wealth and power. In contrast, Britain and France approached the slave trade from purely colonial perspectives: Britain sought to use the slogan of "combating slavery" to expand its maritime and political influence, while France aimed to protect the interests of its agricultural colonies that depended on enslaved labor. As the rivalry between the two European powers intensified, the issue of slavery turned into a tool of political and economic pressure on the rulers of Zanzibar. Despite the treaties and imposed restrictions, the trade continued through covert methods, including smuggling and the use of foreign flags, until the late nineteenth century.
Keywords: Esclavage -- Oman